Early and late outcomes after open ascending aortic surgery: 47-year experience in a single centre - Pan E; Kytö V; Savunen T; Gunn J (My University, 2022)
The aims of the study are to describe the long-term survival of patients undergoing primary open ascending aortic surgery and to portray the evolution of aortic surgery during six decades in a single centre. Included were all 614 patients who underwent primary ascending aortic surgery in 1968–2014 at one Nordic university hospital. Patients were identified and data were collected from patient records and surgical logs. Mortality data were acquired from the national registry. Median follow-up was 11.2 years using reverse Kaplan–Meier method. Overall 30-day survival was 91.2% and for 30-day survivor rates were 86.9, 77.6, 52.1, 38.3 and 26.7% at 5, 10, 20, 30 and 40 years. There was no significant difference in long-term survival for 30-day survivors (p = 0.105) between patients treated emergently for dissection/rupture and electively (mainly ascending aortic aneurysms). On Cox regression era of surgery (p = 0.006), increasing age (p < 0.001) and indication (p < 0.001) were predictors of 30-day mortality. Arch involvement indicated twofold risk (HR 2.09, p = 0.05) compared to non-arch involved. Only increasing age (p < 0.001) predicted long-term mortality. There was a sixfold risk of 30-day mortality in the earliest era compared to the latest (p = 0.03). After the early postoperative phase following ascending aortic surgery, the surgical indication and urgency of the index operation have no significant impact on long-term survival. The very long term survival after ascending aortic surgery is excellent for 30-day survivors and improved through the era. Surgical treatment has improved and perioperative mortality has decreased significantly in 47 years.